EDUCATORS TERMS OF EFFECTIVE COMMUNICATION SKILLS - Tuğba SELANİK AY (Fırat University, 2019)
Education activities which aims to adapt students to the social life and being them as a member of the society which they live occurs in communication environments. In this context effective communication skill is one of the prerequisite skills which provide effective education. The aim of this study is to evaluate the educators’ effective communication skills based on classroom teacher candıdates’ observations. In this study classroom teacher candidates were asked to observe and keep diaries for four weeks. Classroom teacher candidates were asked to observe for educators in terms of effective communication skills and besides observations also they were asked to provide events about communication in their diaries. Classroom teacher candidates’ diaries analyzed though content analyzes and identified their themes which in the diaries. Also the findings supported with direct quotations from the classroom candidates’ observations and views. Examined the results generally positive results for all sub-dimensions for teacher trainers. The results for classroom teachers verbal and non-verbal communication except sub-dimension of diction that made the positive statements. Examined the results about classroom teacher candidates The fluency of speech, tone of voice, use clear expressions, accents and diction sub-dimensions of verbal communication were stated negative expressions; eye contact, distance and physical contact, posture, gestures and facial expressions sub-dimensions of non-verbal communication were stated both negative and positive expressions. But the negative expressions were stated more than the positive ones. Examined the results about school administrators generally included positive statements about verbal communication; as well as these results except eye contact, distance and physical contact sub-dimensions its seen that the majority of positive expressions.